A secreted protease-like protein in Zymoseptoria tritici is responsible for avirulence on Stb9 resistance gene in wheat - Amezrou, Reda; Audéon, Colette; Compain, Jérôme; Gélisse, Sandrine; Ducasse, Aurélie; Saintenac, Cyrille; Lapalu, Nicolas; Louet, Clémentine; Orford, Simon; Croll, Daniel; Amselem, Joëlle; Fillinger, Sabine; et al. (My University, 2023)
Zymoseptoria tritici is the fungal pathogen responsible for Septoria tritici blotch on wheat. Disease outcome in this pathosystem is partly determined by isolate-specific resistance, where wheat resistance genes recognize specific fungal factors triggering an immune response. Despite the large number of known wheat resistance genes, fungal molecular determinants involved in such cultivar-specific resistance remain largely unknown. We identified the avirulence factor AvrStb9 using association mapping and functional validation approaches. Pathotyping AvrStb9 transgenic strains on Stb9 cultivars, near isogenic lines and wheat mapping populations, showed that AvrStb9 interacts with Stb9 resistance gene, triggering an immune response. AvrStb9 encodes an unusually large avirulence gene with a predicted secretion signal and a protease domain. It belongs to a S41 protease family conserved across different filamentous fungi in the Ascomycota class and may constitute a core effector. AvrStb9 is also conserved among a global Z. tritici population and carries multiple amino acid substitutions caused by strong positive diversifying selection. These results demonstrate the contribution of an 'atypical' conserved effector protein to fungal avirulence and the role of sequence diversification in the escape of host recognition, adding to our understanding of host-pathogen interactions and the evolutionary processes underlying pathogen adaptation.